THE EFFECT OF THE QUALITY OF MOTORCYCLE MODIFICATION PRODUCTS FROM REY CUSTOM MOTOSHOP ON CUSTOMER SATISFACTION AND LOYALTY - Hidayatullah, Muhammad Riski; Surur, Miftahus; Agusti (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The title of this study is the effect of product quality at Rey Custom Motoshop motorcycle modification workshop. This study was conducted on customers who modified Prodjie lights on their motorcycles and used the services of Rey Custom Motoshop workshop located on Jalan Banongan Selatan, Gudang Village, Asembagus District, Situbondo Regency. This study used accidental sampling technique. The data were tested using validity tests, reliability tests, hypothesis tests, and research data analysis using descriptive analysis, multiple linear regression analysis, correlation coefficient analysis, and determination analysis